Selective binding and lateral clustering of α5β1 and αvβ3 integrins: Unraveling the spatial requirements for cell spreading and focal adhesion assembly. Issue 5 (2nd September 2016) - Schaufler, Viktoria; Czichos-Medda, Helmi; Hirschfeld-Warnecken, Vera; Neubauer, Stefanie; Rechenmacher, Florian; Medda, Rebecca; Kessler, Horst; Geiger, Benjamin; Spatz, Joachim P.; Cavalcanti-Adam, E. Ada
ABSTRACT: Coordination of the specific functions of α5β1 and αvβ3 integrins is crucial for the precise regulation of cell adhesion, spreading and migration, yet the contribution of differential integrin-specific crosstalk to these processes remains unclear. To determine the specific functions of αvβ3 and α5β1 integrins, we used nanoarrays of gold particles presenting immobilized, integrin-selective peptidomimetic ligands. Integrin binding to the peptidomimetics is highly selective, and cells can spread on both ligands. However, spreading is faster and the projected cell area is greater on α5β1 ligand; both depend on ligand spacing. Quantitative analysis of adhesion plaques shows that focal adhesion size is increased in cells adhering to αvβ3 ligand at 30 and 60 nm spacings. Analysis of αvβ3 and α5β1 integrin clusters indicates that fibrillar adhesions are more prominent in cells adhering to α5β1 ligand, while clusters are mostly localized at the cell margins in cells adhering to αvβ3 ligand. αvβ3 integrin clusters are more pronounced on αvβ3 ligand, though they can also be detected in cells adhering to α5β1 ligand. Furthermore, α5β1 integrin clusters are present in cells adhering to α5β1 ligand, and often colocalize with αvβ3 clusters. Taken together, these findings indicate that the activation of αvβ3 integrin by ligand binding is dispensable for initial adhesion and spreading, but essential to formation of stable focal adhesions.